From Traditional Remedy to Evidence-Based Phytotherapeutic Agent: Hedera helix L. in Respiratory Medicine - Agata Maria Pawłowska (Plants, 2026)
Hedera helix L. leaf extracts are regulated expectorants for productive cough, yet their evidence is dispersed across pharmaceutical quality, nonclinical pharmacology, disposition, toxicology, clinical pharmacology, efficacy, safety, and regulatory assessment. This review integrates those domains in a single study-level account and explicitly distinguishes isolated constituents, incompletely specified extracts, defined monograph preparations, proprietary extracts, and combination products. Hederacoside C is the pharmacopoeial marker, while α-hederin is the constituent most extensively examined in β2-adrenergic receptor models. Cell studies documented reduced agonist-induced receptor internalisation, greater ligand binding and cAMP responsiveness, and altered GRK2/β-arrestin signalling. Isolated tissue and animal studies reported antispasmodic, anti-inflammatory, antitussive, and tracheobronchial secretory effects. Rat studies showed low, matrix-dependent oral exposure to hederacoside C and α-hederin. Small exploratory human studies detected no or only trace α-hederin and did not permit conventional pharmacokinetic analysis. Clinical evidence includes placebo-controlled adult trials, active comparator studies, paediatric investigations, postmarketing cohorts, systematic reviews, and pharmacovigilance reports. Controlled adult trials of EA 575 reported greater short-term improvement in cough or Bronchitis Severity Score than placebo; paediatric efficacy evidence is dominated by observational studies and small airway function trials. Short-term tolerability was generally favourable, with gastrointestinal and hypersensitivity reactions as the principal recognised adverse effects. The European Union monograph recognises specified extracts for productive cough, contraindicates use below two years, and does not recommend use during pregnancy or lactation. The distinctive contribution of this review is the complete quality-to-clinic evidence map, including dose, model, endpoint, study design, extract identity, and unresolved evidence domain for each major dataset.